Pathogen-induced changes in floral scent may increase honeybee-mediated dispersal of Erwinia amylovora - Cellini, Antonio; Giacomuzzi, Valentino; Donati, Irene; Farneti, Brian; Rodriguez-Estrada, Maria T.; Savioli, Stefano; Angeli, Sergio; Spinelli, Francesco (The ISME Journal, 2019)
Honeybees are well recognised for their key role in plant reproduction as pollinators. On the other hand, their activity may vector some pathogens, such as the bacterium Erwinia amylovora , the causative agent of fire blight disease in pomaceous plants. In this research, we evaluated whether honeybees are able to discriminate between healthy and E. amylovora -infected flowers, thus altering the dispersal of the pathogen. For this reason, honeybees were previously trained to forage either on inoculated or healthy (control) apple flower. After the training, the two honeybee groups were equally exposed to inoculated and control flowering apple plants. To assess their preference, three independent methods were used: (1) direct count of visiting bees per time frame; (2) incidence on apple flowers of a marker bacterium ( Pantoea agglomerans , strain P10c) carried by foragers; (3) quantification of E. amylovora populations in the collected pollen loads, proportional to the number of visits to infected flowers. The results show that both honeybee groups preferred control flowers over inoculated ones. The characterisation of volatile compounds released by flowers revealed a different emission of several bioactive compounds, providing an explanation for honeybee preference. As an unexpected ecological consequence, the influence of infection on floral scent increasing the visit rate on healthy flowers may promote a secondary bacterial spread.